The influence of Edward Weston in still life photography / Norhaslinda Shafie - Shafie, Norhaslinda (UiTM Perak Press, 2021)
Presently, our environments fill with thousands of images. Images are dominant to human communication and can view from a variety of forms and styles. Thus, this writing is to produce an overview of the influence of still life elements by Edward Weston helped revolutionize photography so that it became a key component of modern art. This review conducted using qualitative research where the documenting process is involved in visual research analysis. The structure observations were made to identify the general style used by Edward Weston in producing the artwork. This survey concluded that her artwork related to the photo used by a realistic photograph with organic shapes and modern wonders prompted the audience to reconsider objects that looked familiar and form new relationships with them.